2014
DOI: 10.1371/journal.pntd.0003086
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression in Plasmodium knowlesi Malaria Is Linked to Variation in Invasion Gene Family Members

Abstract: Emerging pathogens undermine initiatives to control the global health impact of infectious diseases. Zoonotic malaria is no exception. Plasmodium knowlesi, a malaria parasite of Southeast Asian macaques, has entered the human population. P. knowlesi, like Plasmodium falciparum, can reach high parasitaemia in human infections, and the World Health Organization guidelines for severe malaria list hyperparasitaemia among the measures of severe malaria in both infections. Not all patients with P. knowlesi infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 48 publications
1
69
0
1
Order By: Relevance
“…The Philippine, MR4 and the Hackeri Strains formed a separate group along with Malaysian Borneo isolates. The distinct sub-populations observed in other invasion gene of P. knowlesi like MSP1P, DBPRII, NBPXA and TRAP was not observed in MSP7D [23, 2527, 31, 49]. (Fig.5).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Philippine, MR4 and the Hackeri Strains formed a separate group along with Malaysian Borneo isolates. The distinct sub-populations observed in other invasion gene of P. knowlesi like MSP1P, DBPRII, NBPXA and TRAP was not observed in MSP7D [23, 2527, 31, 49]. (Fig.5).…”
Section: Resultsmentioning
confidence: 91%
“…Studies on mitochondrial and ssrRNA genes in P. knowlesi from patients and wild macaques identified two distinct sub-populations which clustered geographically to Peninsular Malaysia and Malaysian Borneo [23]. Additionally, genetic and genomic studies from Malaysia identified 3 distinct sub-populations; two originating from Sarawak and one from Peninsular Malaysia [2427] thereby highlighting the complexity of infections in humans and the challenges for control as well as vaccine design.…”
Section: Introductionmentioning
confidence: 99%
“…However, even the humanadapted P. knowlesi line invades cynomolgus RBCs more efficiently than human RBCs, suggesting that invasion efficiency may remain a bottleneck in human infections. Interestingly, variation in NBPXb, which had been found not to bind to human RBCs, also has been linked to disease severity in humans (7,16). The role of NBPXb and variants of both P. knowlesi NBPs now can be investigated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Particular alleles of two erythrocyte binding protein genes in P. knowlesi were found to be associated with specific disease progression profiles, such as differences in parasitaemia, and markers of disease severity such as hemoglobin levels, platelet levels, renal dysfunction, etc. in a population of knowlesi malaria patients (Ahmed et al , 2014). These two genes are also known to show differential binding between macaque and human erythrocytes (Semenya et al , 2012).…”
Section: Discussionmentioning
confidence: 99%